The Use Of Ict In Enhancing Students' Interest In Learning English At Sman 16 Batam - Eunike Ester Caraline Wahyudi; Theodesia Lady Pratiwi (ConCEPt - Conference on Community Engagement Project, 2023)
This study aims to integrate ICT media in teaching and learning activities. The participants of the study were 44 students from 11th grade of social sciences and 1 English teacher at Public Senior High School 16 in Batam. This research uses convenience sampling. This study used two research instruments, namely questionnaires and interviews. The students' need analysis questionnaire in the form of Google Form was distributed face to face in the class through their WhatsApp group. The Likert scale used in this needs analysis questionnaire. the interview session conducted through Zoom and the result was in the form and has been transcribed. The collected data can then be used to design lesson plans and integrate technologies into teaching media while considering students' needs. Furthermore, integration of ICT in learning is carried out to determine whether ICT implementation can enhance students' interest in studying English or not.